1988
DOI: 10.1103/physrevb.38.852
|View full text |Cite
|
Sign up to set email alerts
|

Freezing of spin and charge inLa2xSrxCu

Abstract: Zeroand longitudinal-field muon-spin relaxation (it+ SR) measurements have been performed on La2-Sr"Cu04 alloys in both single-crystal and sintered powder forms above and below their magnetic transition temperatures, Tf. The p+ precession frequency v depends only weakly on x and Tf, an observation which together with resistivity data implies classical freezing of magnetic moments in the regime where the carriers are localized. For x 0.05, critical dynamics are observed near Tf. The p SR technique is shown to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
39
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(47 citation statements)
references
References 17 publications
8
39
0
Order By: Relevance
“…A similar magnetic phase diagram has also been reported for La 2−x Sr x CuO 4 and Y 1−x Ca x Ba 2 Cu 3 O 6 [11,12,13]. In conventional spin glasses, magnetic interactions are more or less isotropic in space, and the whole spin system is believed to be frozen in the spin-glass phase [14].…”
supporting
confidence: 76%
“…A similar magnetic phase diagram has also been reported for La 2−x Sr x CuO 4 and Y 1−x Ca x Ba 2 Cu 3 O 6 [11,12,13]. In conventional spin glasses, magnetic interactions are more or less isotropic in space, and the whole spin system is believed to be frozen in the spin-glass phase [14].…”
supporting
confidence: 76%
“…The superconductivity usually does not appear until n ~ 5 to 10%. Therefore, another low-temperature state intervenes; it is usually thought of as an electronic "cluster glass" (ECG) state (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). At higher dopings, the ECG signatures coexist with diminishing intensity with the strengthening superconductivity, until they disappear somewhere near n ~ 15%.…”
mentioning
confidence: 99%
“…At higher dopings, the ECG signatures coexist with diminishing intensity with the strengthening superconductivity, until they disappear somewhere near n ~ 15%. Although the ECG state exhibits no known long range spin or charge order, some electronic order of unknown spatial form is always detected at nm scale by local probes of the spin (8)(9)(10)(11)(12)(13)(14)(15) and charge (14-20) -hence the "cluster" designation. And, because it is from this ECG state that high temperature superconductivity emerges with hole doping (22), it is critical to determine what it is, how it is generated by hole doping, and how it evolves into and coexists with the superconducting state.…”
mentioning
confidence: 99%
“…For such materials the magnetism was found in the series of zero field µSR experiments [28,33,34]. The example of temperature dependence of µSR frequencies in these materials is shown in Fig.…”
Section: "214"mentioning
confidence: 99%
“…Harshman et al [33] extended their μSR studies of La2-x Srx CuO4 onto longitudinal-field decoupling experiments. Especially, for x = 0.05 and temperature just above ordering temperature they found that the μSR signal "is a sum of two components: one (derived from magnetic fluctuations) freezes and yields muon-spin precession at low temperatures, and another (due to a set of apparently stronger moments) that do not yield a precession signal".…”
Section: "214"mentioning
confidence: 99%